CORRELATION BETWEEN MAXILLARY ANTERIOR TOOTH SIZE RATIO AND SMILE ESTHETICS INDEX IN ORTHODONTICS PATIENTS: A CROSS-SECTIONAL ANALYSIS - Sari Kurniawati; Nur Masita Silviana; Astika Swastirani; Yustisian Goretti Nauli (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2026)
Introduction: Aesthetics smile is a crucial aspect of physical appearance that significantly influences self-confidence. The proportion of maxillary anterior teeth size plays an essential role in forming a harmonious smile. The Smile Index serves as a parameter to measure smile characteristics from the frontal dimension.Aim: to determine the relationship between the maxillary anterior teeth size ratio and Smile Index in orthodontic patients at the FKG UB Clinical Laboratory.Methods: This cross-sectional analytical study utilized 32 samples of study models and photometry from orthodontic patients aged 17-30 years who met the inclusion criteria. The anterior teeth size ratio (central incisor, lateral incisor, and canine) was measured using calipers on study models by dividing mesiodistal width by cervicoincisal height. The Smile Index was measured through frontal photometry by dividing intercommissural width by interlabial distance during smiling. Data were analyzed using the Spearman correlation test and simple linear regression with a 95% confidence level.Result: The mean size ratio was 0.88±0.02 for central incisors, 0.87±0.02 for lateral incisors, 0.93±0.02 for canines, and 6.98±0.25 for Smile Index. There was no significant difference between right and left anterior teeth size ratios (p>0.05). Correlation tests showed no significant relationship between central incisor size ratio and Smile Index (r=-0.83; p=0.651), lateral incisor (r=0.33; p=0.858), or canine (r=-0.79; p=0.667). Overall, the anterior teeth size ratio showed no significant relationship with Smile Index (p=0.908).Conclusion: There is no relationship between the maxillary anterior teeth size ratio and Smile Index in orthodontic patients. Anterior teeth do not show a significant relationship either individually or collectively with Smile Index values. This finding suggests that smile aesthetics could be influenced by multiple factors beyond tooth dimensions alone, including soft tissue characteristics and facial proportions.